GROWING CAPPARIS SPINOSA AND THE STUDY OF ITS IMPORTANCE IN TRADITIONAL MEDICINE - UsnatdinovJ.N (Journals Park Publishing, 2022)
The article describes the medicinal properties of Capparis spinosa L., which belongs to the Capparaceae family, as well as its use in folk medicine. In traditional and scientific medicine, information on the use of ancient and modern plants is given. Anti-inflammatory, anti-inflammatory, anti-allergic, neuroprotective, anti-diabetic and anti-diabetic hypolipidemic properties of etilgen.In today's ecological situation, the medicinal and nutritional importance of the capparis spinosa plant has been explained in order to increase the knowledge of young and future people of our country.
Keywords: gewil, in the state of the people, to prepare for the, to calm the nerves